PENERAPAN PE.NDEKATAN INQUIRYDALAM PEMBELAJARAN SAINS SEBAGAI UPAYA PENGEMBANGAN CARA BERPIKIR DIVERGEN - Widowati, Asri (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Formal education until recently tend to teach students to fact memorizing andconvergent thinking. It makes student have difficulties in solving problems thatdemand deep thinking and creative problem solving. Learning process in classtend to expect outcomes as knowledge, memory, and logic thinking. Students needto be motivated to think divergently. This is a serious issue since this kind oflearning might results in reduction or even death of student's creativity.Developing creativity in science education, especially those that related tostudent's divergent thinking ability, require learning approaches that willencourage students to think well and able to give many alternative solutions to asingle problem. Inquiry approach is the most effective one since this approach isstudent centered and persuades students to solve problem using scientific skillsand researches. In other wordr, inquiry approach is a wcy in developingdivergent thinking